Psychometric properties of the Five-Digit Test in patients with stroke. Issue 1 (2nd January 2016) - Lin, Gong-Hong; Lu, Yi; Wu, Chien-Te; Chiu, En-Chi; Huang, Sheau-Ling; Hsueh, I-Ping; Hsieh, Ching-Lin
Abstract: Purpose : To examine the ecological validity, predictive validity, and responsiveness of the Five Digit Test (FDT) in patients with stroke. Methods : We included inpatients with stroke ( n = 144, 114 and 105 in the ecological validity, predictive validity, and responsiveness analysis, respectively) in the study. At admission, the FDT and Barthel Index (BI) were assessed; at discharge, the FDT, BI, Postural Assessment Scale for Stroke Patients (PASS), and Mobility Subscale of the Stroke Rehabilitation Assessment of Movement (MO-STREAM) were assessed. Results : In the ecological validity analysis, the scores of the selective and alternating attention indices of the FDT were moderately correlated with those of the BI at admission and discharge (Spearman ρ = –0.38 to –0.45). In the predictive validity analysis, the scores of the two attention indices of the FDT at admission were moderately correlated with the scores of the BI, PASS, and MO-STREAM at discharge ( ρ = –0.33 to –0.45). In the responsiveness analysis, the two attention indices of the FDT between admission and discharge had large differences (success rate difference = 0.56–0.67, Wilcoxon Z = –5.90 to –6.60). Conclusion : Our results indicate that the selective and alternating attention indices of the FDT have acceptable ecological validity, predictive validity, and good responsiveness in patients with stroke. Implications for Rehabilitation: The Five Digit Test (FDT), an efficient and culture-free assessment tool, has been used to assess selective attention and alternating attention The selective index and alternating attention index of the FDT showed acceptable ecological validity, predictive validity, and good responsiveness in patients with stroke.